The risks to education systems from design mismatch and global isomorphism: Concepts, with examples from India - Lant Pritchett (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The incredibly low levels of learning and the generally dysfunctional public sector schooling systems in many (though not all) developing countries are the result of a capability trap (Pritchett et al. 2010). Two phenomena reinforce persistent failure of schooling systems to produce adequate learning outcomes. One is the mismatch between system design - the allocation of activities across organizations and mechanisms of accountability - and the insights of the 'new institutional economics' from principal agent models and contract theory. In particular, many education systems attempt to manage teaching and learning as a 'thin' or 'logistical' activity that can be managed with top-down control and an emphasis on compliance. The reality is that teaching is a 'thick' or 'implementation intensive' activity that performs better when teachers and operators of schools are given performance standards, have multiple in-depth accountability channels, and are given greater autonomy. The second phenomena that facilitates persistent failure is global isomorphism on enrollment and inputs (Meyer et al. 1977; Boli et al. 1985; Meyer et al. 1997). That is, the field (in the sense of Bourdieu 1993) of global education has produced a near exclusive emphasis on enrollments and duration in school, adequacy of physical inputs, and formal qualifications that allowed, perhaps encouraged, national systems to ignore completely performance on child-learning (of any type, measured in any way). I conclude with a comparison in India of the national governments recent efforts in basic education which have been almost exclusively isomorphic.
Keywords: I20; I25; L14; L32; 330; education; institutions; systems